Mainstreaming Climate-Smart Agriculture and Climate Information Services into Universities’ Curricula: Training of West Africa University Lecturers - Bamba, Adama; M’Bo, Kacou; Kone, Ismaïla; Amoutchi, Amien Isaac; Koné, Daouda (2023)
As part of the AICCRA project, the West African Science Service Centre on Climate Change and Adapted Land Use (WASCAL) and the Regional Universities Forum for Capacity Building in Agriculture (RUFORUM) are mandated to develop curricula and training materials to accelerate the mainstreaming of climate information services (CIS) and climate-smart agriculture (CSA) into university curricula in Africa. This report presents the activities of a training of trainers (ToT) workshop on the Soil Carbon Sequestration and Crop Production course module led by WASCAL as part of the AICCRA curriculum development activities. The training program was held in Abidjan, Côte d'Ivoire, from September 19 to 21, 2023. Seventy-eight (78) university lecturers, including 28% women, from seven West African countries, benefited from the training programme. University institutions, civil society organisations and technical bodies working in the field of agriculture were represented. The curricula consisted of four sessions on (i) soils for sustainable crop production, (ii) climate change and crop production, (iii) soil carbon sequestration, and (v) spatial estimation and modelling of soil carbon. The training programme was designed with a participant-centred approach. Overall, the training workshop contributed to improving participants' knowledge of climate-smart agriculture and climate information services. There is a need for monitoring to track the outcomes of this training and how it helps to mainstream CSA and CIS into universities curricula.